“Towards the Connection Between Humans and Nature”: A Critique of the Myths of Stone Castles in Ecocritical Contexts - Sarakool, Charun; Hongsuwan, Pathom (Journal of Ecohumanism, 2024)
This paper explores the complex relationship between the myths surrounding stone castles and ecological dimensions in Thailand, focusing on Northeastern Thailand. Stone castles are historical and artistic symbols and representations of the deep connection between humans and their natural environment. These myths, rooted in folklore, convey community histories and cultural identities, highlighting the struggles and triumphs of past civilizations. The storytelling related to stone castles emphasizes sustainable practices and respect for natural resources, fostering a sense of unity and pride within communities. Using an ecocritical lens, this study examines the significance of these stone monuments beyond their artistic value, revealing the sustainable practices and environmental awareness of ancient peoples. By analyzing these myths, we gain insight into the values and beliefs that shaped human interactions with nature throughout history. The myths illustrate a legacy of ecological respect and balanced coexistence with the environment, offering crucial lessons for contemporary society on the importance of environmental conservation and cultural preservation. Ultimately, this critique highlights the need to appreciate and understand the ongoing relationship between humans and nature, as reflected in the myths of stone castles.